Ethologically based behavioural and neurochemical characterisation of mice with isoform-specific loss of dysbindin-1A in the context of schizophrenia. (25th September 2020) - O'Tuathaigh, Colm M.P.; Desbonnet, Lieve; Payne, Christina; Petit, Emilie; Cox, Rachel; Loftus, Samim; Clarke, Gerard; Cryan, John F.; Tighe, Orna; Wilson, Steve; Kirby, Brian P.; Dinan, Timothy G.; et al.
Highlights: Ethologically based behavioural and neurochemical characterisation were carried out in dysbindin-1A (Dys-1A) gene knockout mice. Female Dys-1A mice showed increased social investigation and exploratory behaviour but intact problem-solving performance. Monoamine analysis revealed lower levels of 5-HT in ratio to its metabolite 5-HIAA in the prefrontal cortex. Abstract: Dysbindin-1 is implicated in several aspects of schizophrenia, including cognition and both glutamatergic and dopaminergic neurotransmission. Targeted knockout of dysbindin-1A (Dys-1A KO), the most abundant and widely expressed isoform in the brain, is associated with deficits in delay/interference-dependent working memory. Using an ethologically based approach, the following behavioural phenotypes were examined in Dys-1A KO mice: exploratory activity, social interaction, anxiety and problem-solving ability. Levels of monoamines and their metabolites were measured in striatum, hippocampus and prefrontal cortex using high-performance liquid chromatography with electrochemical detection. The ethogram of initial exploration in Dys-1A KO mice was characterised by increased rearing from a seated position; over subsequent habituation, stillness was decreased relative to wildtype. In a test of dyadic social interaction with an unfamiliar conspecific in a novel environment, female KO mice showed an increase in investigative social behaviours. Marble burying behaviour was unchanged. Using the puzzle-box test to measure general problem-solving performance, no effect of genotype was observed across nine trials of increasing complexity. Dys-1A KO demonstrated lower levels of 5-HT in ratio to its metabolite 5-HIAA in the prefrontal cortex. These studies elaborate the behavioural and neurochemical phenotype of Dys-1A KO mice, revealing subtle genotype-related differences in non-social and social exploratory behaviours and habituation of exploration in a novel environment, as well as changes in 5-HT activity in brain areas related to schizophrenia.